Keterampilan Guru dalam Pengelolaan Kelas pada Mata Pelajaran Fikih Kelas VII di MTsN 3 Agam - Gunawan, Indra; Wati, Salmi (Lembaga Yasin AlSys, 2023)
The author's motivation in discussing this title is motivated by problems in classroom management skills that are preventive and curative by fiqh teachers. Based on the initial observations, the authors know that the teacher pays little attention to the behavior of students and approaches students, when there are students who make a fuss, the teacher only reprimands them from the front but does not approach the students so that not long after that the students make a fuss again. The purpose of this study was to describe the teacher's classroom management skills related to the creation and maintenance of optimal (preventive) learning conditions for class VII at MTsN 3 Agam. To describe the teacher's classroom management skills related to the restoration of curative learning conditions for class VII at MTsN 3 Agam. To describe class management skills related to the physical condition of class VII at MTsN 3 Agam. This research uses a type of field research (field research) using a qualitative descriptive approach. This research was conducted at MTsN 3 Agam, IV Koto sub-district, Agam district, West Sumatra. The informants of this study were fiqh teachers and class VII students at MTsN 3 Agam. Collecting research data using observation techniques, interviews, and documentation. The results showed that: Teacher skills in classroom management related to the creation and maintenance of optimal learning conditions (preventive in nature) for class VII at MTsN 3 Agam which were carried out by the teacher had been carried out in accordance with the indicators of classroom management skills, although there were several indicators that were less than optimal and rarely carried out, namely indicators of observing closely and moving closer. The teacher's classroom management skills related to returning optimal (curative) learning conditions for class VII at MTsN 3 Agam have been well implemented, namely the teacher modifies student behavior, solves problems in groups, and finds and solves behaviors that cause problems. The teacher's skills in class management related to the physical condition of class VII at MTsN 3 Agam have been well implemented, namely the teacher has made arrangements for seats, managed class cleanliness, ventilation and lighting in the class.